Growth of left ventricular mass with military basic training in army recruits. - Batterham, A; George, K; Birch, K; Pennell, D; Myerson, S (2011)
UNLABELLED: Exercise-induced left ventricular hypertrophy is well documented, but whether this occurs merely in line with concomitant increases in lean body mass is unclear. PURPOSE: Our aim was to model the extent of left ventricular hypertrophy associated with increased lean body mass attributable to an exercise training program. METHODS: Cardiac and whole-body magnetic resonance imaging was performed before and after a 10-wk intensive British Army basic training program in a sample of 116 healthy Caucasian males (aged 17-28 yr). The within-subjects repeated-measures allometric relationship between lean body mass and left ventricular mass was modeled to allow the proper normalization of changes in left ventricular mass for attendant changes in lean body mass. To linearize the general allometric model (Y=aXb), data were log-transformed before analysis; the resulting effects were therefore expressed as percent changes. We quantified the probability that the true population increase in normalized left ventricular mass was greater than a predefined minimum important difference of 0.2 SD, assigning a probabilistic descriptive anchor for magnitude-based inference. RESULTS: The absolute increase in left ventricular mass was 4.8% (90% confidence interval=3.5%-6%), whereas lean body mass increased by 2.6% (2.1%-3.0%). The change in left ventricular mass adjusted for the change in lean body mass was 3.5% (1.9%-5.1%), equivalent to an increase of 0.25 SD (0.14-0.37). The probability that this effect size was greater than or equal to our predefined minimum important change of 0.2 SD was 0.78-likely to be important. CONCLUSIONS: After correction for allometric growth rates, left ventricular hypertrophy and lean body mass changes do not occur at the same magnitude in response to chronic exercise.